Contraceptive prevalence in Montserrat - Jagdeo, Tirbani P. (International Planned Parenthood Federation New YorkUS, 1985)
Discusses the general family planning situation in Montserrat and highlights fertility rates, fertility performance and preference of women aged 15-44. Assesses the knowledge of contraceptives methods and outlets looking particularly at barriers to contraceptive use. Outlines patterns of contraceptive use focussing on socio-demographic characteristics of sexually active women; the factors influencing the timing of the first and current contraceptive use and preferred methods and sources of contraception among users. Examines the extent to which family planning programmes affect the levels of contraceptive use in Montserrat. Examines internal and social sources of resistance to contraception among non users in Montserrat.